The James Webb Space Telescope: the golden opportunity to unlock the secrets of our Universe (2024)
The James Webb Space Telescope, which has generated stunning images recently, is a landmark in astronomy because of its history of international collaboration and costly development, underscoring its importance in advancing our understanding of the cosmos as science progresses.